DEVELOPING TASK-BASED LANGUAGE TEACHING, POST-METHOD ERA AND LEARNING OUTSIDE THE CLASSROOM COMPETENCE (Academicia Globe: Inderscience Research, 2022)
The following graduation project work deals with the issue of communicative teaching methods, mainly TBLT (Task-Based Language Teaching) approach, which are one of the most fundamental problems of modern EFL teaching. Unlike other methods, Task-Based Language teaching offers an alternative for language teachers. A natural context is developed from the students' experiences with the language that is personalized and relevant to them. The main focus of this approach is the process rather than the product. Learners learn language by interacting communicatively and pur-posefully while engaged in the activities and tasks. Activities and tasks can be either: those that learners might need to achieve in real life; those that have a pedagogical purpose specific to the classroom.